Perkembanagan Jiwa Beragama Pada Anak, Remaja dan Orang Dewasa - Hully, Muhammad Taqiyuddin, Mustahiqqurahman (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
This paper examines the problem of the development of the religious spirit in children, adolescents and adults. This is very important because the development of the religious spirit in children is not the same when entering adolescence and adulthood. The potential of the religious spirit in children has existed since in the womb, after being born it requires a stimulus from the family, school and community environment in its development. The development of religion in adolescents is in line with physical and psychological development which is then marked by mental shock and a critical attitude in adolescents towards religious teachings. However, in everyday reality, there are still many adults who feel mental shock. Even changes in beliefs and beliefs sometimes still occur. This is also what attracts the attention of religious experts, so they try to continue to invite and provide understanding about religion and faith in Allah. Adult religious attitudes are more broadly based on values ​​and a deep understanding of religious teachings. Religion for adults is an attitude of life and not just a part of it. The methodology used is descriptive qualitative literature research, namely analyzing theories from authentic sources (books) and up to date sources. From the results of the studies conducted, it is shown that the development of the religious spirit in children is characterized by an attitude of imitation, then starting from the level of fairy tales, reality and individualism. In adolescents, the development of the religious spirit starts from the attitude of joining in, believing with awareness, indecision and distrust. While the development of the religious soul in adults. Characterized by accepting the truth with full consideration or not joining in, being realistic and positive, open and more critical. So, the development of the religious spirit in children, adolescents and adults is not the same or different along with the level of development.